(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of learning models and creativity on the learning outcomes of lower passing in volleyball games. The sample of this study amounted to 44 people who were seventh-grade students of SMP Negeri 2 Lubuk Pakam using a 2 x 2 treatment by level research design. The data were analysed using analysis of variance and continued with the Tukey test at the significance level α = 0.05. The results showed 1) in general, there was a significant difference between the STAD-type cooperative learning model and direct learning model (Qo 4.13 > Qt 3.90). 2) For students with high creativity, the STAD cooperative learning model is better than the direct learning model (Qo 11.5 > Qt 4.26). 3) For students with low creativity, the STAD cooperative learning model is better than the direct model (Qo 5.45 > Qt 4.26). 4) There is an interaction between the learning model and creativity on learning outcomes of lower passing in volleyball game (Fo 27.22 > Ft 4.06)